Multiwavelength coverage of the 2024 periastron passage of PSR B1259-63/LS 2883 - Chernyakova, M.; Malyshev, D.; van Soelen, B.; Finn Gallagher, A.; Matchett, N.; Russell, T. D.; van den Eijnden, J.; Lower, M. E.; Johnston, S.; Tsygankov, S.; Salganik, A.; Shebalkova, Iu (OXFORD UNIV PRESS, 2025)
PSR B1259-63is a gamma-ray binary system with a 48 ms radio pulsar orbiting around an O9.5Ve star, LS 2883, in a highly eccentric similar to 3.4 yr long orbit. Close to the periastron the system is detected from radio up to the TeV energies due to the interaction of the stellar wind from LS 2883 and the pulsar's relativistic outflow. Observations of the last four periastron passages, taken in 2010-2021, demonstrate periastron-to-periastron variability at all wavelengths, probably linked to the state of the Be star's decretion disc. In this paper, we present the results of our optical, radio and X-ray observational campaigns on PSR B1259-63 performed in 2024 accompanied with the analysis of the publicly available GeV Fermi/LAT data. We show that this periastron passage was characterized by the early flaring of X-rays before the periastron passage and GeV emission after the periastron passage, which can be explained by a larger size of the decretion disc as supported by the optical observations. The structure of the GeV flare is also in agreement with the disruption of the large dense disc. The possible X-ray/radio correlation was observed only during the post-periastron rise of X-ray and radio emission.